2015
DOI: 10.1128/genomea.01120-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Nine Phages Capable of Infecting Paenibacillus larvae, the Causative Agent of American Foulbrood Disease in Honeybees

Abstract: We present here the complete genome sequences of nine phages that infect Paenibacillus larvae, the causative agent of American foulbrood disease in honeybees. The phages were isolated from soil, propolis, and infected bees from three U.S. states. This is the largest number of P. larvae phage genomes sequenced in a single publication to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…92% similarity with the TLS of vB_BceS-IEBH (YP_002154374.1) and 80% with the TLS of A118 (NP_463463.1) [ 20 , 23 ]. The TLS of PfEFR-4 and 11143 revealed 77% and 46% similarity, respectively, with that of Paenibacillus phage Harrison (YP_009193815.1), which has site-specific packaging with “cohesive ends with 3’ overhangs” [ 24 ]. The TLS of Tp250 shared 85% similarity with that of PBC1 (YP_006383455.1), which carries terminally redundant and partially permuted genomes [ 25 ], thus Tp250 might also have a headful packaging mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…92% similarity with the TLS of vB_BceS-IEBH (YP_002154374.1) and 80% with the TLS of A118 (NP_463463.1) [ 20 , 23 ]. The TLS of PfEFR-4 and 11143 revealed 77% and 46% similarity, respectively, with that of Paenibacillus phage Harrison (YP_009193815.1), which has site-specific packaging with “cohesive ends with 3’ overhangs” [ 24 ]. The TLS of Tp250 shared 85% similarity with that of PBC1 (YP_006383455.1), which carries terminally redundant and partially permuted genomes [ 25 ], thus Tp250 might also have a headful packaging mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that the majority of these isolates were genetically unique. 42 GenBank accession numbers for 9 of the phages are as follows: KT361649, KT361650, KT361651, KT361652, KT361653, KT361654, KT361655, KT361656, KT361657.…”
Section: Resultsmentioning
confidence: 99%
“…Assembly was carried out using Geneious 7.1 (Biomatters, Auckland, NZ). 38 Details of the assembly process are given in 26 .…”
Section: Methodsmentioning
confidence: 99%
“… 40 We also used GeneMark.hmm ( exon.gatech.edu ). 41 Details of the annotation procedure are given in 26 .…”
Section: Methodsmentioning
confidence: 99%